Different influences of Mo and Mo2C additions on microstructure and properties of TiC-based cermets - Xiao-Dong Kang; Guo-Hua Zhang; Kuo-Chih Chou (Journal of Materials Research and Technology)
Composite Mo–Mo2C powders with varying contents of Mo and Mo2C were synthesized through in situ carbothermal reduction of MoO3 followed by hydrogen reduction. TiC-10(Mo + Mo2C)–10WC–20Ni (wt%) cermets were produced using self-synthesized TiC and Mo–Mo2C composite powders as well as WC and Ni powders. All sintered samples exhibited a uniformly distributed core-rim structure. As the proportion of Mo2C in composite powder increased, the rim of cermets became thinner, and the grain size was finer. The hardness of cermets increased with increasing Mo2C content in composite powders, and decreased with extended holding time. In contrast, the fracture toughness (KIC) of cermets exhibited the opposite trend. The transverse rupture strength (TRS) initially increased but then decreased as the increase of Mo2C content. Sintered sample using composite powder of Mo-94.1 wt% Mo2C exhibited the smallest grain size of 0.66 μm and the highest hardness of 1576 HV30 after sintering for 0.5 h. Whereas, the sintered sample of TiC–10Mo–10WC–20Ni demonstrated the highest KIC of 16.44 MPa m1/2 and a hardness of 1449 HV30 after a sintering time of 2 h. As the Mo2C content in composite powder increased, the fracture mechanism of cermets changed from a mixed mode of intergranular fracture and transgranular fracture to predominantly intergranular fracture, resulting in a reduction in KIC. The complexity of fracture morphology was quantified via the fractal dimension. Sintered samples with simpler fracture morphologies had smaller fractal dimensions, whereas those with more intricate surface features exhibited larger fractal dimensions, reflecting complex fracture mechanisms and higher TRS.